2000
DOI: 10.1001/archsurg.135.11.1273
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Liver and Portal Vein Resection for Hepatocellular Carcinoma With Tumor Thrombi Extending to Portal Bifurcation

Abstract: Background: The role of surgical resection for hepatocellular carcinoma with tumor thrombi involving the major portal vein is controversial because of a high operative risk and poor prognosis. Previously, a resection was performed only when the tumor thrombi were limited to the first branch of the portal vein without extension to the portal bifurcation. Hypothesis: Concomitant liver and portal vein resection may be beneficial in patients with hepatocellular carcinoma with tumor thrombi extending to portal bifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 19 publications
2
72
0
Order By: Relevance
“…A median survival ranging from 8.9 to 33 months was reported for HCC with PVTT with surgical treatment. [13][14][15][16][17][18][19] Although these results seems to be superior to TACE, patients who received HR were highly selected. We, therefore, conducted this casematch-control study comparing HR with TACE in the treatment of HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A median survival ranging from 8.9 to 33 months was reported for HCC with PVTT with surgical treatment. [13][14][15][16][17][18][19] Although these results seems to be superior to TACE, patients who received HR were highly selected. We, therefore, conducted this casematch-control study comparing HR with TACE in the treatment of HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, after HR, there was one postoperative in-hospital death caused by postoperative liver failure (0.5%), and the major complication rate was 4.0% (8 of 201), our results were similar to the studies reported previously. [13][14][15][16][17][18][19][20][21][22] Therefore, HR is still a safe treatment for HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported 5-year survival reached around 40 % (1, 2). Right or left hemihepatectomy with segmental resection of the main portal vein has been applied for HCC with PVTT extending into the main portal trunk or the contralateral portal vein, using several modified surgical techniques (3,4). This procedure is considered to be an en bloc resection.…”
Section: How I Do Itmentioning
confidence: 99%